Depresija in sladkorna bolezen - Klemenčič, Simona (Zdravniški vestnik, 2008)
Background The prevalence of depression among diabetic patients is twice as high as in the general population. Conclusions The authors want to turn attention to this problem, considering also the previous findings of epidemiological surveys, and try to explain the possible causes of comorbidity. Biological, psychological, and socio-economic factors concerning the interrelation between depression and diabetes are discussed in more detail. The authors emphasize the co-influence between the diseases, which cancomplicate the treatment or accelerate the progression of both of them, especially when depression in diabetic patients is not recognized, and is consequently not properly treated. Basic approaches to treatment of depressivesymptoms in diabetic patients based on the use of antidepressants and cognitive behavioral therapy are described.
Keywords: dejavniki tveganja; depresija (medicina); Depresivna motnja; Depressive Disorder; Diabetes Mellitus; Sladkorna bolezen